ASYMMETRIC SYNTHESIS OF (S)-β-(3,4-DIMETHYLPHENYL)-α-ALANINE (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
An efficient method of asymmetric synthesis of (S)-N-(2-benzoylphenyl)-1-(2-chlorbenzyl)pyrrolidine-2-carboxamide via asymmetric C-alkylation of Ni(II)- complex of Schiff’s base with glycine and chiral auxiliary reagent (S)-N-(2-benzoylphenyl)-1-(2-chlorbenzyl)pyrrolidine-2-carboxamide by 3,4-dimethylbenzylchloride with following decomposition of the diastereomer complexes and isolation of the target optically active amino acid has been developed. The stereoselectivity of the C-alkylation reaction exceeds 91% and the optically purity of the isolated target α-amino acid – (S)-3,4-dimethylphenylalanine – 99%.
Keywords: Ni(II)- complex of Schiff’s base; glycine; asymmetric synthesis; (S)-3,4-dimethylphenylalanine; diastereomer